Mutual Fund Flows at Long Horizons - Bessembinder, Hendrik; Chen, Shuaiyu; Cooper, Michael J; Xue, Jinming; Zhang, Feng (Review of Financial Studies, 2026)
Abstract We show that positive flows to active mutual funds with high recent returns partially reverse at longer horizons. This outcome is robust across a broad range of alternative specifications. Reversal occurs from greater outflows associated with high prior returns, not reduced inflows. We test theories to explain the reversal: investment life cycles, tax loss selling, and a behavioral “disappointment” hypothesis based on investors’ overreaction to positive returns. While both tax loss selling and short investor life cycles can contribute, the evidence supports a role for investor disappointment, whereby investors redeem their capital when return performance fails to meet expectations.